Verification, validation and testing in software engineering - Dasso, Aristides, 1943-; Funes, Ana, 1964- (Idea Group Pub., 2007)
"This book explores different applications in V & V that spawn many areas of software development -including real time applications- where V & V techniques are required, providing in all cases examples of the applications"--Provided by publisher.